Relevansi Prinsip Filsafat Pendidikan Islam terhadap Demokratisasi Pendidikan di Indonesia - Salma Kusuma Listiani; Abdul Khobir; Rosalina; Baihaqi (STKIP Subang, 2025)
This study aims to analyze the relevance of the principles of Islamic Educational Philosophy to the process of democratization of education in Indonesia. The democratization of education is understood as an effort to create equal access and learning opportunities for all citizens, in line with the values ​​of justice, equality, deliberation, and respect for human dignity, which are fundamental principles in Islamic teachings. Using qualitative research methods with a library study, this study examines literature related to the concept of democratization of education, the values ​​of Islamic educational philosophy, and various problems in implementing democratization in Indonesia. The results show that the democratization of education in Indonesia still faces obstacles in the form of unequal access, an authoritarian learning culture, a mismatch between policy and implementation, the challenges of the digital era, and the degradation of moral and spiritual values. The principles of Islamic education such as monotheism, shura, justice, moderation, and the obligation to seek knowledge offer a philosophical and normative foundation to strengthen the democratization of education to be more inclusive, humanistic, and oriented towards character building. This study confirms that the integration of Islamic values ​​in the national education system can be a solution in realizing education that is fair, participatory, and relevant to current developments.